Pemutihan Karang di Perairan Laut Natuna Bagian Selatan tahun 2010 - Rudi, Edi (Universitas Jambi, 2012)
Mass coral bleaching is caused by high sea surface temperatures (SST). SST in theNatuna Sea have risen rapidly since late April 2010 and caused mass coral bleaching. This research wascarried out on 14 sites in Tambelan and Serasan Islands, southern Natuna Sea on November 2010. Dataof colony number and coral genera of the bleaching coral were collected using 10 x 2 m2 belt transect atreef slope, 4 – 6 meter depth below sea level. Each transect was replicated three times on each site.The research found 13 genera of bleaching coral. The bleaching coral number ranged from one to sevencolonies/transect. Acropora and Porites suffered the highest bleaching number and occurred on all sites.The highest degree of bleaching coral was occurred on the Manggirang Besar in Tambelan Islands.Over the course of data collection, bleaching in the Southern Natuna Sea was low and did not indicatethe presence of mass coral bleaching. However, the results confirm that a large number of dead coralwith algae (DCA) indicating that many corals might have been bleached approximately since July 2010.We urge the need to perform local and global actions such as promoting marine protected areas toconserve reef ecosystem especially in the southern Natuna.